Public Investment in Bolivia : Prospects and Implications - Endegnanew, Yehenew (IMF Working Papers; Working Paper ;, 2019)
Bolivia's 'Patriotic Agenda 2025' sets targets for social and economic development propelled by state-led industrialization under a five-year development plan (2016-2020). Large-scale public investment has aimed to fill infrastructure gaps and raise productivity to ensure sustained medium-term growth. Pursuit of these goals in a period of lower hydrocarbon revenues has, however, contributed to widening fiscal and external current account deficits. The paper uses a structural model to outline different scenarios for the level of public investment in the face of declining hydrocarbon revenues. It finds that if public investment is sustained at current levels as a share of GDP while hydrocarbon revenues continue to decline, the sustainability of the public debt could be called into question.